Strategies of federated Apaes to impact the education and assistance of exceptionals in Brazil: A historical analysis between the years 1960 and 1970 - Giovani Ferreira Bezerra (Arizona State University, 2020)
This text discusses strategies mobilized by Apaean leaders in their work in the field of exceptionality, with a view to obtaining public attention, political power and financial resources from the Brazilian federal government before the creation of the National Center for Special Education (Cenesp), in 1973. Historical and documentary research is used, compiling the data through legislation and documents issued by the government, newspapers of general circulation, edited during the 1960s and 1970s, as well as copies of the periodical Mensagem da Apae from 1963 to 1973. It was evident that the Apaean leaders acted with the power established during the military governments installed after 1964, expanding their network of influences and having some government support. Based on national and international contingencies designed in the early 1970s, the creation of Cenesp established a new dynamic in the field of Special Education, which became officially designated and institutionalized, directed and regulated by the federal government, although private-philanthropic interference in the direction of this educational modality has not ceased.